Bahasa Indonesia Bahasa Indonesia - Maria Magdalena Setyaningsih (Jurnal Keperawatan Malang, 2015)
Umbilical cord care with the open method is the umbilical cord care in case of sterile, clean, dry withoutadding any chemical substances (alcohol) and not closed the meeting with anything. If not done well andright time oxcel becomes longer, and infections. Further conditions can lead to Tetanus Neonatorum. Thisresearch aims to know the behavior of the mother in the care of the umbilical cord with the open method.Design research used descriptive observational. The population is all of the mothers who gave birth inhospital Nursing Waluya Malang on 11-17 may 2015 with Purposive Sampling technique using a samplenumber of 10 respondents. The data was processed using T-scores and results of research of 10 respondentswho researched, obtained the data respectively as 6 respondents (60%) are not able and 4 respondents(40%) are able to do the cord care with the open method. Mother's previous experience and habit ofneighbourhood in the treatment of the open method of the umbilical cord became supporters of theoccurrence of a behavior. The giving of information and guidance method using emphasis on umbilical cordcare application method open to mothers is indispensable to change the behavior of the mother. Key words:Granuloma Umbilicalis, Umbilical Cord Care